Luciobarbus lanigarensis and L. numidiensis, two new species of barbels from the Mediterranean Sea basin in North Africa (Teostei: Cyprinidae) - Brahimi, Amina; Libois, Roland; Henrard, Arnaud; Freyhof, Jörg (Zootaxa, 2018)
Two new species of Luciobarbus are described from the Mediterranean Sea basin in Morocco and Algeria. Their monophyly and phylogenetic placement are resolved by molecular analyses using two mitochondrial markers (cyt b and D-loop). Luciobarbus lanigarensis, new species, from the Tafna River drainage in Algeria and Morocco, is distinguished by having orange fins, a great predorsal length (52–59% SL) and a very long pectoral fin (79–90% HL). Luciobarbus numidiensis, new species, from the El-Kébir River drainage in Algeria, is distinguished by having a golden pectoral-fin margin, 43–47+1–3 lateral line scales and a very long anal-fin (19–23%).